Potentiale nutzen und Verbindungen herstellen: Neue fachliche Aufgabenbereiche für Bibliotheken am Beispiel Forschungsdatenmanagement - Auberer, Benjamin; Berg-Weiß, Alexander; Gabriel, Vanessa; Spenger, Martin (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2022)
This article discusses the opportunities and challenges for academic libraries in the context of changing requirements and tasks due to digitization. These developments are viewed through the lens of the professional group of academic librarians, more specifically the subject librarian. Existing structures, especially the subject librarian departments, play a crucial role in these developments, as they offer opportunities to efficiently and adequately address new topics within their institution. However, when subject librarians take on new tasks, there is a need for self-assurance in order to react adequately to new situations. Using the example of research data management (RDM) at the University Library of LMU, new possibilities like a cooperation between RDM services, subject librarians and researchers are emerging. What role do concepts such as “Embedded Librarian” or “Data Literacy” play in the context of RDM? And how can subject librarians be involved to successfully improve the RDM structures of their institutions?
Keywords: Subject Librarian; Embedded Librarian; Research Data; Research Data Management; Data Literacy